Efektivitas LMS pada Pembelajaran Matematika Berbasis Daring: Kajian Meta Analisis: Meta Analisis - Miftahul Ilmi; Endang Suprapti; Sandha Soemantri (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
Online learning or the application of e-learning is currently widely applied near all schools in Indonesia. One of the applications of e-learning is the use of LMS which is an integrated and comprehensive system and can be used as an e-learning platform. Meta-analysis was used in this study by examining several scientific studies in national journals. Meta-analysis is quantitative because it uses the calculation of numbers and statistics for practical purposes, namely to compile and extract information from so much data that is impossible with other methods. From several subjects that have been taken, it shows that the application of LMS is more effectively used at the high school education level than the junior high school education level. The application of LMS has the highest positive effect on blended learning methods among other methods. Then on the subject the type of LMS used. The effectiveness of the application of LMS in mathematics learning was found that the use of Schoology had a greater influence than other types of LMS.